OPTIMALISASI PEMANFAATAN BARANG MILIK NEGARA UNTUK MENDUKUNG PENINGKATAN PENERIMAAN DAN EFISIENSI ANGGARAN PADA KEMENTERIAN/LEMBAGA - Taswin Taswin (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2025)
State Property is all goods purchased or obtained at the expense of the APBN and other legitimate acquisitions. There is a condition of State Property in Ministries/Institutions that is less productive, has not been utilized or has less than optimal utilization so that optimization is needed in the form of utilization. Minister of Finance Regulation Number 115/PMK.06/2020 states that utilization is the utilization of State Property that is not used for carrying out the duties and functions of Ministries/Institutions and/or optimizing State Property without changing the ownership status. The research method used is a normative juridical approach to explore applicable provisions and a descriptive approach to assess how optimization of the use of State Property is carried out. There are 6 forms of utilization of State Property which can produce two things, namely budget efficiency and Non-Tax State Revenue. Budget efficiency is obtained from the costs of maintaining and securing State Property and budget efficiency for the construction of buildings, facilities and infrastructure. Utilization of State Property also produces Non-Tax State Revenue as a budgetary function, which is one of the instruments of state income outside of tax revenues and grants